Janice VanCleave's constellations for every kid : easy activities that make learning science fun. - VanCleave, Janice Pratt (New York : J. Wiley, 1997)
Describes twenty of the most prominent constellations, including the Big Dipper, Orion, and Cancer; explains how to locate them; and provides instructions for related activities.
"Exciting ideas, projects, and activities for schools, science fair, and just plain fun!"--Cover.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
4.8.
Keywords: Astronomy -- Observers' manuals -- Juvenile literature; Constellations -- Juvenile literature; Astronomy -- Observers' manuals; Constellations; Astronomy; Constellations